Mobility model detection method based on birth and death model in DTN environment - ENGGuang-hong D; AOWan-hua C; HANGJian Z; HENGXiong C; ENGLi F (Tongxin xuebao)
A mobility model detection method based on birth and death model (MMD-BDM) in DTN environment was proposed.It first computed the connected channel capacity of sampling times according to the data traffic during the data transfer process,and then constructed the time varying intercommunication metrics at local,which composed of channel capacity between local node and others.Based on these,the connection birth and death mode of nodes based on connected edges was deduced,and then the birth and death features of the connected nodes was analyzed to detect the mobility model,which used to improve the routing strategy during the packages deliver process.Ultimately,the mobility model detection method was put into use in spray and wait routing (SWR) method and random network coding routing (RNCR) method to experiment,the simulation results show that,it can improve the opportunity routing performance of the data deliver rate and transfer latency in DTN environment.